2009
DOI: 10.1111/j.1460-9592.2009.03130.x
|View full text |Cite
|
Sign up to set email alerts
|

Salbutamol premedication in children with a recent respiratory tract infection

Abstract: The results from this audit suggest that children with a history of a recent RTI have significantly less PRAE following a premedication with salbutamol compared with no premedication. Therefore, premedication with salbutamol might be considered in children with recent RTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 33 publications
0
47
0
3
Order By: Relevance
“…The incidence of perioperative laryngospasm varies widely in the literature from 0.1 to 16 %, primarily due to differences in its definition [20,39]. While perioperative laryngospasm occurs in approximately 4 % of children in a general pediatric population [8,13], smaller frequencies have been reported in retrospective studies or when only severe forms have been reported (e.g., laryngospasm triggering a ''call for help'') [1, 2 • , 17, 39, 40, 41 •• ], whereas greater frequencies have been reported in children with associated risk factors (Table 1).…”
Section: Laryngospasm Epidemiologymentioning
confidence: 98%
See 2 more Smart Citations
“…The incidence of perioperative laryngospasm varies widely in the literature from 0.1 to 16 %, primarily due to differences in its definition [20,39]. While perioperative laryngospasm occurs in approximately 4 % of children in a general pediatric population [8,13], smaller frequencies have been reported in retrospective studies or when only severe forms have been reported (e.g., laryngospasm triggering a ''call for help'') [1, 2 • , 17, 39, 40, 41 •• ], whereas greater frequencies have been reported in children with associated risk factors (Table 1).…”
Section: Laryngospasm Epidemiologymentioning
confidence: 98%
“…Premedication Premedication with beta-2 agonists is recommended for all children with moderate or severe asthma or in those who are actively wheezing due to reactive airway disease (e.g., upper respiratory tract infection) in order to reduce the risk of PRAE [20,82,83].…”
Section: Bronchospasm Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that laryngospasm was always occurred due to the increase of respiratory secretions, the mechanical irritations of endotracheal tube and the effects of anesthetic drugs, as well as the upper respiratory tract infections/potential infection and the suppression of mucociliary clearance by dry airflow during ventilation [6][7][8]. The occurrence of laryngospasm could bring rapid deterioration in systemic oxygenation and cyanosis, and decrease in surplus pulse O 2 (SpO 2 ), even become lifethreatening if some interventions were delayed [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Additional short acting β-agonists are indicated regardless of disease level, as benefits counteracting the bronchial constrictive response to tracheal intubation have been demonstrated [29,[43][44][45][46][47]. Preoperative anxiolytics such as midazolam assist in mitigating anxiety-induced bronchospasm [48].…”
Section: Preoperative Managementmentioning
confidence: 99%